Equity and the Informational Basis of Collective Choice - D'Aspremont, Claude; Gevers, Louis (Review of Economic Studies, 1977)
Journal Article Equity and the Informational Basis of Collective Choice Get access Claude D'Aspremont, Claude D'Aspremont Faculté des Sciences Economiques et Sociales, Namur Search for other works by this author on: Oxford Academic Google Scholar Louis Gevers Louis Gevers Faculté des Sciences Economiques et Sociales, Namur Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 44, Issue 2, June 1977, Pages 199–209, https://doi.org/10.2307/2297061 Published: 01 June 1977